Liver biopsy revealing anti-neutrophil cytoplasmic antibody-associated vasculitis: a tale for a challenging diagnosis - Bahaeddine Lahbacha; Abir Chaabane; Wafa Garbouj; Roua Mankai; Amina Bani; Amal Khsiba; Raja Amri; Salwa Nechi; Emna Chelbi (Future Science OA)
A 62-year-old woman presented with a chronic fever and fatigue. Biological investigations showed leukocytosis and elevation of acute phase markers. Liver blood tests showed deterioration with both cholestatic and hepatocellular patterns (there were, respectively, elevations in serum alkaline phosphatase levels as well as in serum alanine and aspartate aminotransferases). Viral serologies were negative. Mycobacterial infection and endocarditis were excluded. Results from blood cultures were negative. Autoantibody tests including ANCA (anti-neutrophil cytoplasmic antibody), anti-nuclear, anti-smooth muscle and anti-mitochondria were all negative. A liver biopsy revealed epithelioid granulomatous necrotizing vasculitis. Subsequently, immunological testing was repeated revealing MPO-ANCA (myeloperoxidase-ANCA). A diagnosis of ANCA-associated vasculitis with liver involvement was then made. The patient was started on steroids and her clinical state gradually improved.